Aborting feedlot heifers with Alfaprostol - L.E. Keay; G. Kiracofe; M. Simon; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1983)
The effectiveness of alfaprostol in inducing abortion was tested in 93 pregnant heifers. Alfaprostol was injected intramuscularly, .7 mg per 100 pounds body weight. Twenty-four heifers were injected when they averaged 83 days (range 64 to 86) pregnant, while 23 were injected when 138 days (range 119-143) pregnant. A control injection of the Alfaprostol carrier, propylene glycol, was given 23 heifers averaging 81 or 134 days pregnant. By 14 days after the Alfaprostol injection 79% of the heifers 83 days pregnant and 96% of the heifers 138 days pregnant had aborted. Two of the 83-day controls and none of the 138 day controls aborted. Since Alfaprostol (5.4 mg) was very effective up to at least 140 days of pregnancy, but somewhat less effective earlier, the dosage may need to be increased for lighted or earlier pregnancy heifers. No serious side effects were noted in aborted heifers.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Abortion; Pregnant; Body weight